Mild fever as a catalyst for consumption of the ischaemic penumbra despite endovascular reperfusion. Issue 2 (28th July 2020) - Dehkharghani, Seena; Yaghi, Shadi; Bowen, Meredith T; Pisani, Leonardo; Scher, Erica; Haussen, Diogo C; Nogueira, Raul G
Abstract: Cerebrovascular ischaemia is potentiated by hyperthermia, and even mild temperature elevation has proved detrimental to ischaemic brain. Infarction progression following endovascular reperfusion relates to multiple patient-specific and procedural variables; however, the potential influence of mild systemic temperature fluctuations is not fully understood. This study aims to assess the relationship between systemic temperatures in the early aftermath of acute ischaemic stroke and the loss of at-risk penumbral tissues, hypothesizing consumption of the ischaemic penumbra as a function of systemic temperatures, irrespective of reperfusion status. A cross-sectional, retrospective evaluation of a single-institution, prospectively collected endovascular therapy registry was conducted. Patients with anterior circulation, large vessel occlusion acute ischaemic stroke who underwent initial CT perfusion, and in whom at least four-hourly systemic temperatures were recorded beginning from presentation and until the time of final imaging outcome were included. Initial CT perfusion core and penumbra volumes and final MRI infarction volumes were computed. Systemic temperature indices including temperature maxima were recorded, and pre-defined temperature thresholds varying between 37°C and 38°C were examined in unadjusted and adjusted regression models which included glucose, collateral status, reperfusion status, CT perfusion-to-reperfusion delay, general anaesthesia and antipyretic exposure. The primary outcome was the relative consumption of the penumbra, reflecting normalized growth of the at-risk tissue volume ≥10%. The final study population comprised 126 acute ischaemic stroke subjects (mean 63 ± 14.5 years, 63% women). The primary outcome of penumbra consumption ≥10% occurred in 51 (40.1%) subjects. No significant differences in baseline characteristics were present between groups, with the exception of presentation glucose (118 ± 26.6 without versus 143.1 ± 61.6 with penumbra consumption, P = 0.009). Significant differences in the likelihood of penumbra consumption relating to systemic temperature maxima were observed [37°C (interquartile range 36.5 − 37.5°C) without versus 37.5°C (interquartile range 36.8 − 38.2°C) with penumbra consumption, P = 0.001]. An increased likelihood of penumbra consumption was observed for temperature maxima in unadjusted (odds ratio 3.57, 95% confidence interval 1.65 − 7.75; P = 0.001) and adjusted (odds ratio 3.06, 95% confidence interval 1.33 − 7.06; P = 0.009) regression models. Significant differences in median penumbra consumption were present at a pre-defined temperature maxima threshold of 37.5°C [4.8 ml (interquartile range 0 − 11.5 ml) versus 21.1 ml (0 − 44.7 ml) for subjects not reaching or reaching the threshold, respectively, P = 0.007]. Mild fever may promote loss of the ischaemic penumbra irrespective of reperfusion, potentially influencing successful salvage of at-risk tissue volumes following acute ischaemic stroke. Abstract : We certify that all authors have reviewed and approve the contents of the manuscript, that the Brain requirements for authorship have been met, and that the following materials are not under review elsewhere. All related, preceding works are cited and no significant overlaps are present. The corresponding author, Seena Dehkharghani, wishes to disclose receipt of modest travel support by iSchemaview within the preceding 12 months. There are no other relevant conflicts; however, the full list of author disclosures is included at the conclusion of the manuscript body. Graphical Abstract: